Dengue virus and Plasmodium coinfection among febrile patients in Osun State, Nigeria - BABAJIDE B. AJAYI; KEHINDE S. OLAITAN; OLUWATOBA F. OWOYOMI; SUNDAY E. ONI; AKINWALE M. AKINLABI; ELIZABETH O. ARO; DAVID O. OGBOLU (Smujo International, 2025)
Abstract. Ajayi BB, Olaitan KS, Owoyomi OF, Oni SE, Akinlabi AM, Aro EO, Ogbolu DO. 2025. Dengue virus and Plasmodium coinfection among febrile patients in Osun State, Nigeria. Nusantara Bioscience 17: 253-258. Dengue and malaria are major co-endemic vector-borne diseases in Nigeria, presenting significant diagnostic challenges due to their overlapping clinical symptoms. In settings where malaria is hyperendemic, febrile illnesses are often presumptively treated as malaria, potentially leading to the misdiagnosis of other pathogens like dengue virus (DENV). This study aimed to determine the seroprevalence of DENV infection and the prevalence of DENV/Plasmodium coinfection among febrile patients in Osun State, Nigeria. A cross-sectional study was conducted from April to September 2024, involving 250 febrile patients from selected healthcare facilities. Blood samples were analyzed using rapid diagnostic tests (RDTs) for Plasmodium antigens and for DENV-specific Immunoglobulin M (IgM) and G (IgG) antibodies. Sociodemographic and risk factor data were collected via structured questionnaires. The prevalence of malaria was high at 53.6% (134/250), consistent with the region's hyperendemic status. Evidence of recent DENV infection (IgM positive) was found in 0.8% (2/250) of patients, while 6.4% (16/250) were IgG positive, indicating past exposure. Concurrent infection was detected in 0.8% (2/250) of patients for Malaria/DENV IgM and 3.2% (8/250) for Malaria/DENV IgG. Both malaria and DENV IgG seropositivity were significantly associated with age (p<0.05). This study confirms the endemic circulation of DENV in Osun State and highlights its contribution to the burden of non-malarial febrile illness. These findings underscore the critical need to revise existing diagnostic algorithms and integrate DENV surveillance into public health frameworks to mitigate misdiagnosis and improve patient outcomes.